PEMBINAAN TARTIL AL-QURâ€™AN METODE TILAWATI DI IBU - IBU AISYIYAH RANTING JOGODALU BENJENG GRESIK - Muyasaroh Muyasaroh (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This dedication is motivated by the urgency of reading the Qur'an as part of Muslim worshipÂ« ÙˆÙŽØ§ÙŒÙ„ÙŽØ°ÙÙŠ ÙŠÙŽÙ‚ÙØ±Ø§ÙŒ Ø§Ù„Ù‚ÙØ±Ø§Ù†ÙŽ ÙˆÙŽÙŠÙŽØªÙŽØªÙŽØ¹ØªÙŽØ¹Ù ÙÙÙŠÙ‡ ÙˆÙŽÙ‡ÙÙˆÙŽ Ø¹ÙŽÙ„ÙŽÙŠÙ‡Ù Ø´ÙŽØ§Ù‚ÙŒ Ù„ÙŽÙ‡ Ø§ÙŽØ¬ÙŽØ±Ø§Ù† Â» Ù…ØªÙÙ‚ÙŒ Ø¹Ù„ÙŠÙ‡Rasulullah said,